Satellite-derived Sea Level Height Trend and Variation associated with Eastern Little Tuna (Euthynnus affinis) catch rates in the Makassar Strait - Syamsuddin, Mega L.; Puspita, Ajeng; Syamsudin, Fadli; Sunarto; T. Sofyana, Neng (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2026)
Sea level is a key oceanographic variable that exhibits both spatial and temporal variability and serves as an important indicator of global and regional ocean–climate variability, which can influence fishery productivity. Using satellite observation data, this study aimed to identify patterns and fluctuations in sea level trends and variability, and to examine their effects on the catch rates of Eastern Little Tuna (Euthynnus affinis) in the Makassar Strait over a ten-year period (2013–2022). Sea level time series were generated through averaging calculations and spatial mean mapping to characterize sea level distribution. Histogram analysis was applied to determine the frequency of catch per unit effort (CPUE) across different sea level ranges. The results showed that mean sea level in the Makassar Strait during the study period ranged from 0.48 to 0.78 m. Clear annual and seasonal sea level variability was observed, with higher values (0.65–0.70 m) during the northwest monsoon and lower values (0.50–0.60 m) during the southeast monsoon. Over the ten-year period, sea level increased by approximately 0.13 m. The highest CPUE of Eastern Little Tuna was associated with sea levels between 0.60 and 0.65 m. Histogram analysis further indicated that this sea level range corresponded to the maximum CPUE values. In contrast, higher sea levels ranging from 0.75 to 0.80 m were associated with the lowest CPUE, value of 30 kg/trip.